Self-bonding of semi-crystalline PEEK by nano thin film polymer coatings facilitated by multiple plasma depositions. (January 2020) - Awaja, Firas; Wong, Tsz-ting; O'Brien, Timothy
Abstract: Self-bonding of PEEK is an enabling process for the use of PEEK for devices that require hermetic seals such as active medical implants. Self-bonding of semi-crystalline polyether ether ketone (PEEK) has been successfully demonstrated through plasma immersion ion implantation and deposition (PIIID) treatment. The surface properties, such as wetting property, free energy, and roughness, of PEEK that influence the adhesive strength are manipulated according to the ionization power and excitation reactivity of the plasma gas implemented in the treatment. Temperature, one of the self-bonding process condition parameters, is a factor influencing the functionalities of the plasma gas. In general, the combinations of plasma gases, C2 H2, CH4, and O2, were capable of achieving at least fivefold adhesive strengths of PEEKs with only CH4 plasma gas showing a negative response. Single O2 /CH4 - and C2 H2 -PIIID plasma treatments performed effectively in enhancing the adhesive strength of PEEK with almost eightfold compared to untreated control while double C2 H2 /O2 +O2 /CH4 -PIIID/PIIID plasma treatment obtained an equivalent achievement.